Television buyers in the digital era: A comparative study of the UK and Spain. (October 2019) - Navarro, Celina; Prado, Emili
European television channels harbour a significant amount of imported programmes within their schedules. This presence, with its social and cultural impact, is directly affected by the established practices of the television industry which conditions the type and origin of the foreign programmes that are being acquired by linear broadcasters. This research article aims to analyse the criteria used by local television buyers when acquiring international programmes and understand the reasons behind transnational television flows. The findings of the interviews with the television buyers of the main free-to-air television corporations of the United Kingdom and Spain reveal that there is a high level of standardization across the two countries in the decision making process and this homogenizes the range of programme viewers are exposed to. However, a differentiation between public and commercial channels has to be made since public broadcasters consider social and cultural aspects to a higher degree.